Efecto antioxidante del aloe vera (Aloe barbadensis miller) en el proceso de refrigeración del semen porcino en parámetros de calidad espermática - Intriago Macías, Walther José (2022)
The objective of this research was to evaluate the protective and antioxidant effect of aloe vera (Aloe barbadensis miller) in the process of cooling boar semen on sperm quality parameters. A Yorshire x Topig breeding pig was collected, the Friedman test was applied, the treatments being: T0 without addition, Androstar® Plus; T1: BTS+50μ; T2:BTS+100μ, T3:BTS+150μ, aloe vera on ml of semen. The variables to be measured were: vitality, motility, normality, morphology, normal and damaged apical edge, cytoplasmic droplet and cost-benefit. Porcine sperm quality showed that the best treatment was T3 with 84.29% motility versus T0 with 87.29%; vitality T3 obtained 79.29% and T0 obtained 82.62% on average; and the normality of the T3 spermatozoa reached 84.29% and the T0 achieved 85.24%; with a sperm quality of Androstar ± 3% better; the functionality of the sperm membrane indicated that the Normal Apical Border at T3= 97.57% compared to 97.81% at T0, is ± 0.24% higher; on the part of the Normal Cytoplasmic Gout the T3= 97.29% and the T0= 97.52%; being 0.23% higher; In addition, it is evident that the proximal and distal cytoplasmic droplets have the same tendency; so it is concluded that the antioxidant BTS+150μ aloe vera is very close to Androstar; In terms of cost/benefit, it has favorable effects valued at $0.95 per dose compared to Androstar whose value per dose is $1.76; the latter being 46% more expensive.